Ankylosing spondylitis: etiology, pathogenesis, and treatments - Zhu, Wei; He, Xuxia; Cheng, Kaiyuan; Zhang, Linjie; Chen, Di; Wang, Xiao; Qiu, Guixing; Cao, Xu; Weng, Xisheng (Bone Research, 2019)
Ankylosing spondylitis (AS), a common type of spondyloarthropathy, is a chronic inflammatory autoimmune disease that mainly affects spine joints, causing severe, chronic pain; additionally, in more advanced cases, it can cause spine fusion. Significant progress in its pathophysiology and treatment has been achieved in the last decade. Immune cells and innate cytokines have been suggested to be crucial in the pathogenesis of AS, especially human leukocyte antigen (HLA)‑B27 and the interleukin‑23/17 axis. However, the pathogenesis of AS remains unclear. The current study reviewed the etiology and pathogenesis of AS, including genome-wide association studies and cytokine pathways. This study also summarized the current pharmaceutical and surgical treatment with a discussion of future potential therapies.